2021
DOI: 10.3389/fmicb.2021.673216
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Multiplex PCR Assay for Genotyping the Fish Pathogen Piscirickettsia salmonis Through Comparative Genomics

Abstract: Piscirickettsia salmonis is a bacterial pathogen that severely impact the aquaculture in several countries as Canada, Scotland, Ireland, Norway, and Chile. It provokes Piscirickettsiosis outbreaks in the marine phase of salmonid farming, resulting in economic losses. The monophyletic genogroup LF-89 and a divergent genogroup EM-90 are responsible for the most severe Piscirickettsiosis outbreaks in Chile. Therefore, the development of methods for quick genotyping of P. salmonis genogroups in field samples is vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…For all experiments, P. salmonis colonies were grown in AUSTRAL-SRS broth (ASB) at 18°C for 120 h and 75 rpm ( Yañez et al., 2012 ). The identity of each isolate was confirmed by phenotyping procedures and PCR assays ( Karatas et al., 2008 ; Isla et al., 2021 ). Bacterial cell density was measured using the BacLight™ LIVE/DEAD Viability Kit (Invitrogen™, USA).…”
Section: Methodsmentioning
confidence: 99%
“…For all experiments, P. salmonis colonies were grown in AUSTRAL-SRS broth (ASB) at 18°C for 120 h and 75 rpm ( Yañez et al., 2012 ). The identity of each isolate was confirmed by phenotyping procedures and PCR assays ( Karatas et al., 2008 ; Isla et al., 2021 ). Bacterial cell density was measured using the BacLight™ LIVE/DEAD Viability Kit (Invitrogen™, USA).…”
Section: Methodsmentioning
confidence: 99%
“…( 46 ) showed that P. salmonis isolated in different parts of the world, including the reference strain LF-89, are closely related to each other (over >99% similarity in their 16S, ITS and 23S genes), but the Chilean isolate EM-90 is unique and genetically divergent from the others. Later, these findings were confirmed with more evidence from evaluations of their genomic structures and phylogenetic relationships to support the existence of two genogroups of P. salmonis , LF-89 and EM-90 ( 44 , 47 52 ). P. salmonis pangenome LF-89 and EM-90 show 148 and 273 unique proteins, respectively ( 44 ), and different geographical distribution patterns and susceptibilities of salmon species have been described ( 53 ).…”
Section: Piscirickettsia Salmonis : a Fastidious Bacteriummentioning
confidence: 68%
“…This notion has also been experimentally supported by studies based on multilocus sequence typing (MLST) and PCR amplification of 16S rRNA genes followed by restriction fragment length polymorphism (PCR-RFLP) typing ( 51 , 54 ). Although different real-time TaqMan ® PCR assays have been used for several years by private diagnostic laboratories to identify and discriminate between LF-89 and EM-90 isolates in the Chilean salmon industry, a multiplex PCR protocol to differentiate both genogroups has recently been reported ( 52 ). P. salmonis can survive ≥120 h and replicate in cell cultures enriched with Atlantic salmon macrophages ( 55 ).…”
Section: Piscirickettsia Salmonis : a Fastidious Bacteriummentioning
confidence: 99%
“…Two P. salmonis strains were studied: the LF-89 (ATCC VR-1361) wild type and the EM-90-like (Ps007) strain. The identity of each isolate was confirmed via phenotyping and polymerase chain reaction (PCR) assays (Isla et al, 2021;Karatas et al, 2008). Cultures were grown on tryptone soy with haemoglobin (Austral-TSHem) agar plates at 18°C for 10 days (Yáñez et al, 2013) or in AUSTRAL-SRS broth (ASB) at 18°C for 120 h with moderate agitation (75 rpm) (Yañez et al, 2012).…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…Cultures were grown on tryptone soy with haemoglobin (Austral-TSHem) agar plates at 18°C for 10 days (Yáñez et al, 2013) or in AUSTRAL-SRS broth (ASB) at 18°C for 120 h with moderate agitation (75 rpm) (Yañez et al, 2012). The identity of each isolate was confirmed by phenotyping and PCR assays (Isla et al, 2021;Karatas et al, 2008).…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%